Promotion of Ammonia Electrooxidation on Pt nanoparticles by Nickel Oxide Support. (20th December 2016) - Ntais, Spyridon; Serov, Alexey; Andersen, Nalin I.; Roy, Aaron J.; Cossar, Emily; Allagui, Anis; Lu, Zhenzhen; Cui, Xiaoyu; Baranova, Elena A.; Atanassov, Plamen
Highlights: Pt nanoparticles supported on NiO and MnO2 were synthesized by sacrificial support method. Shift in Pt4f photoemission electron spectra is found for Pt/NiO and Pt/MnO2 . Ammonia electrooxidation (AmER) is more favourable on Pt/NiO (vs. Pt/C and Pt/MnO2 ). Electronic effect between Pt and NiO support is responsible for the higher catalytic activity for AmER. Abstract: In this study Pt nanoparticles supported on NiO, MnO2, and on carbon black were prepared and tested for the ammonia electrooxidation reaction (AmER) in alkaline media. The morphology and structure of the catalysts were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), x-ray diffraction (XRD), nitrogen physisorption, and their surface properties were studied using synchrotron radiation photoelectron spectroscopy (SRPES). Cyclic voltammetry, chronoamperometry and Tafel plots were used to study the electrochemical behavior of ammonia on Pt/metal oxide catalysts. Pt/NiO showed the highest current density and the lowest onset potential for AmER (-0.48 V vs. Hg/HgO) which increased in the order Eonset (Pt/NiO) < Eonset (Pt/MnO2 ) < Eonset (Pt/C). The reaction kinetic order with respect to the concentration of ammonia is close to zero, indicating fast surface adsorption of ammonia in agreement with previous studies on polycrystalline Pt electrodes, whereas the apparent Tafel slopes were found higher (56 − 69 mV dec −1 ) than previously reported values for Pt (39 mV dec −1 ). Our results show that the nature of the support strongly influences the size and electronic properties of the Pt nanoparticles, and as a result their electrocatalytic activity for AmER.